The efficacy of rituximab in the treatment of refractory chronic inflammatory demyelinating polyneuropathy in children: A report of three cases from Northern Vietnam - Van, Nguyen Thi Bich; Dung, Le Thi Thuy; Phuong, Vu Thu; Hung, Cao Vu; Huong, Do Thanh; Van, Nguyen Thi; Tuan, Ta Anh; Nguyet, Dao Thi (Tạp chí Nghiên cứu Y học, 2024)
Rituximab has been reported to be effective in patients with refractory CIDP, especially those with IgG4 autoantibodies against nodal and paranodal proteins. This study reports the clinical characteristics of three cases diagnosed with refractory CIDP successfully treated with rituximab, although testing for IgG4 antibodies is currently not available in Vietnam. Patients were evaluated using the MRC (Medical Research Council Scale for Muscle Strength) and INCAT (Inflammatory Neuropathy Cause and Treatment) scores before and after rituximab treatment. The duration of the disease before rituximab treatment ranged from 6 to 10 months, with total MRC scores of 16 - 26 points, INCAT scores of 8 - 9 points, and the first response noted after 1 - 4 months. Patients recovered well after a follow-up period of 8 to 12 months without adverse effects, with MRC and INCAT scores improving to 48 - 58 points and 1 - 2 points, respectively. Rituximab may be effective in treating refractory CIDP patients.